Ageing and ageism: the impact of stereotypical attitudes on personal health and well-being outcomes and possible personal compensation strategies. (3rd April 2017) - Robertson, Guy
ABSTRACT: Ageism largely remains a socially tolerated form of discrimination. From birthday cards to anti-ageing advertisements and comedy sketches, stereotypical ideas about older people and the ageing process abound. While generally trivialized in mainstream culture, this article argues that ageism is, in fact, a serious matter. Drawing from a growing evidence base, the article highlights the significant and largely detrimental impact that ageist stereotypes have on people's outcomes in later life. It then goes on to analyse some of the possible mechanisms through which stereotypes generate this effect, and finally concludes with a brief outline of some of the psychosocial interventions that might enable older people to weaken or neutralize the toxic effects of internalized negative self-perceptions of ageing. Note: the structural and power relationship dimensions of ageism, while hugely important, are not considered within this article as its focus is on the psychological and emotional dimensions and their impact on personal health and well-being outcomes, an aspect of ageist stereotyping that is seldom discussed.